2019
DOI: 10.1002/jctb.6265
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of CO2 absorption with ionic liquids in a membrane contactor, study of absorption kinetics and influence of temperature

Abstract: BACKGROUND This work presents a comprehensive study of carbon dioxide (CO2) capture from CO2/N2 mixtures in a hollow fiber membrane contactor (HFMC). The absorbents considered were three different ionic liquids (ILs): 1‐ethyl‐3‐methylimidazolium acetate ([emim][OAc]), 1‐ethyl‐3‐methylimidazolium ethylsulfate ([emim][EtSO4]) and 1‐ethyl‐3‐methylimidazolium methyl sulfate ([emim][MeSO4]). A comprehensive two‐dimensional (2D) mathematical model for the transport of CO2 was developed and solved for steady‐state an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 80 publications
(207 reference statements)
0
18
0
Order By: Relevance
“…The sensitivity analysis indicated that at higher vacuum applied in the MVR system, which corresponds to higher desorption efficiencies, the Henry constant variability was less important, as the sensitivity of the model to this parameter was more critical when the desorption efficiencies were low. into account e tchemical equilibrium between CO2 and [emim][Ac] [39,40]. Our reference was the Henry constant calculated in our work ( = 8.8) by a correlation proposed by Hospital-Benito et al [44], which was known to be very successful for the estimation of Henry constant for CO2 absorption in imidazolium ILs.…”
Section: Model Validationmentioning
confidence: 82%
See 4 more Smart Citations
“…The sensitivity analysis indicated that at higher vacuum applied in the MVR system, which corresponds to higher desorption efficiencies, the Henry constant variability was less important, as the sensitivity of the model to this parameter was more critical when the desorption efficiencies were low. into account e tchemical equilibrium between CO2 and [emim][Ac] [39,40]. Our reference was the Henry constant calculated in our work ( = 8.8) by a correlation proposed by Hospital-Benito et al [44], which was known to be very successful for the estimation of Henry constant for CO2 absorption in imidazolium ILs.…”
Section: Model Validationmentioning
confidence: 82%
“…Additionally, a sensitivity analysis of Henry’s constant ( ) of CO 2 in [emim][Ac] (Equation (11)) and pre-exponential factor (B) of the first-order reaction rate constant (Equation (2)) were performed since these parameters were the ones with more uncertainty based on the literature. Just as an example, Henry’s constant is in the range of 0.0051 to 9.3 MPa because some studies do not take into account e tchemical equilibrium between CO 2 and [emim][Ac] [ 39 , 40 ]. Our reference was the Henry constant calculated in our work ( = 8.8) by a correlation proposed by Hospital-Benito et al [ 44 ], which was known to be very successful for the estimation of Henry constant for CO 2 absorption in imidazolium ILs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations